Sex differences in body composition in non‐demented individuals with autosomal dominant Alzheimer's disease: Prevention (nonpharmacological) / Lifestyle factors (e.g., smoking, etc.). (7th December 2020) - Ramirez‐Gomez, Liliana A; Fuller, Joshua T; Rabin, Jennifer S; Bocanegra, Yamile; Guzman‐Velez, Edmarie; Vila‐Castelar, Clara; Pardilla‐Delgado, Enmanuelle; Schoemaker, Dorothee; Gatchel, Jennifer R; Baena, Ana; Giraldo‐Chica, Margarita; Munoz, Claudia; et al.
Abstract: Background: Body mass index (BMI) is a known risk factor for Alzheimer's disease (AD). Research with autosomal dominant Alzheimer's disease (ADAD) has shown a relationship between lower BMI, greater amyloid burden and worse memory performance in presymptomatic mutation carriers. Women have a higher incidence of AD, and may be more susceptible to AD‐ related pathology. However, little is known about the effects of sex/gender on BMI in individuals at increased risk for AD. As carriers of ADAD mutations are destined to develop early‐onset dementia, they allow us to investigate sex differences without aging confounds known to vary by sex (i.e., life expectancy, menopause). We sought to examine sex differences in BMI in non‐demented mutation carriers and non‐carriers from a Colombian kindred with ADAD. Method: 191 carriers of the Presenilin‐1 E280A mutation (104 females; age range: 18‐55 years) and 261 age‐matched non‐carriers (165 females) were included. All participants completed clinical and cognitive assessments, including BMI (kg/m2) measures, MMSE and CERAD Word List tests. Mann‐Whitney‐U test was used to examine sex differences on BMI. General linear models were used to examine the associations between BMI, MMSE and memory, controlling for age and education. Result: Compared to non‐carriers, carriers had lower BMI (carriers: 23.05 +/‐ 3.65; non‐carriers: 24.26 +/‐ 3.92, p=0.002). In carriers, lower BMI was associated with worse performance on MMSE (r=0.49, p=0.001). Compared to male carriers, female carriers had greater BMI (males: 22.4 +/‐ 3.3, females: 23.5 +/‐ 3.7, p=0.04), and performed worse on the MMSE (males: 28.19 +/‐1.8, females: 27.91 +/‐1.91, p=0.04). There was a trend for female carriers to also have worse memory performance (p=0.06). Sex differences were not observed in non‐carriers. There were no associations between BMI and memory. Conclusion: There are sex differences in body composition in carriers of ADAD without dementia. These findings suggest that changes in BMI may reflect early signs of abnormal systemic responses to AD‐related pathology. Future studies should examine longitudinal changes in BMI, from preclinical to clinical stages, and other contributing factors (e.g. vascular risk factors and sex hormones) to determine the potential role of BMI as a risk factor for dementia.